Response of Global Runoff Components to Rising CO2 - Hao Wang; Xiaomang Liu; Kaiwen Wang; Changming Liu (Earth's Future)
Abstract Rising atmospheric CO2 is anticipated to influence global runoff through its radiative effect and physiological effect, thereby resulting in profound impacts on water availability and security. While existing literature has explored the two effects on global total runoff, there is still a lack of attention to changes in runoff components (surface and subsurface runoff). Here, based on idealized 1% yr−1 CO2 increase experiments and 14 Earth system models, we decouple the two effects on changes in runoff components and disentangle the contributions of three influencing factors, namely water supply, atmospheric water demand, and vegetation regulation, which are closely intertwined with the two effects. Global total runoff is expected to increase with rising CO2, and this increase mainly comes from subsurface runoff, leading to an elevated subsurface runoff ratio. Vegetation regulation emerges as the most important factor for the increase in subsurface runoff ratio, with the contribution of 49.3%, followed by water supply (41.7%) and atmospheric water demand (8.9%). Increased total runoff implies potentially more flood risk, while the increase in subsurface runoff ratio could decrease some of the risk. The results indicate the necessity of emphasizing changes in subsurface runoff under climate change.